Analysis on the Temporal and Spatial Heterogeneity of Factors Affecting Urbanization Development Based on the GTWR Model: Evidence from the Yangtze River Economic Belt - Wenbo Ma; Weiteng Tian; Qian Zhou; Qianqian Miao (Complexity)
Revealing the key influencing factors in urbanization is of great significance to the operability of national urbanization planning and decision-making. Taking 110 cities in the Yangtze River Economic Belt (YREB) as the sample, this paper explores the driving mechanism of urbanization development during 2007–2016 by using Geographically and Temporally Weighted Regression Model (GTWR). The results show that the effects of the four dominant factors of social economy, education, secondary industry, and living environment are in line with expectations, with strong time fluctuation, obvious spatial nonstationarity, and a certain spatial gradient distribution. The formulation and implementation of the urbanization strategy should be based on the driving mechanism shown by the four models, coordinate the use of relevant policies, and give priority to ensuring the effective play of the primary driving factors.